(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
This paper discusses the impact of regulation on clinical practice, with specific attention being given to issues of confidentiality and the increasing responsibilities now being imposed upon counsellors and psychotherapists. It argues that practitioners should be wary of placing policies and directives above the privacy of those seeking their help.